Renal Damage Frequency in Patients with Solitary Kidney and Factors That Affect Progression - T. Basturk; Y. Koc; Z. Ucar; T. Sakaci; E. Ahbap; E. Kara; F. Bayraktar; M. Sevinc; T. Sahutoglu; A. Kayalar; A. Sinangil; C. Akgol; et al. (International Journal of Nephrology)
Background. The aim of this study is to assess renal damage incidence in patients with solitary kidney and to detect factors associated with progression. Methods. Medical records of 75 patients with solitary kidney were investigated retrospectively and divided into two groups: unilateral nephrectomy (group 1) and unilateral renal agenesis/dysplasia (group 2). According to the presence of kidney damage, each group was divided into two subgroups: group 1a/b and group 2a/b. Results. Patients in group 1 were older than those in group 2 (p=0.001). 34 patients who comprise group 1a had smaller kidney size (p=0.002) and higher uric acid levels (p=0.028) than those in group 1b at presentation. Uric acid levels at first and last visit were associated with renal damage progression (p=0.004, 0.019). 18 patients who comprise group 2a were compared with those in group 2b in terms of presence of DM (p=0.038), HT (p=0.003), baseline proteinuria (p=0.014), and uric acid (p=0.032) levels and group 2a showed higher rates for each. Progression was more common in patients with DM (p=0.039), HT (p=0.003), higher initial and final visit proteinuria (p=0.014, for both), and higher baseline uric acid levels (p=0.047). Conclusions. The majority of patients with solitary kidney showed renal damage at presentation. Increased uric acid level is a risk factor for renal damage and progression. For early diagnosis of renal damage and reducing the risk of progression, patients should be referred to a nephrologist as early as possible.